2002
DOI: 10.1073/pnas.072525199
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic nanodots from atomic Fe: Can it be done?

Abstract: Laser focusing of Fe atoms offers the possibility of creating separate magnetic structures on a scale of 10 nm with exact periodicity. This can be done by using the parabolic minima of the potential generated by a standing light wave as focusing lenses. To achieve the desired 10-nm resolution, we need to suppress chromatic and spherical aberrations, as well as prevent structure broadening caused by the divergence of the incoming beam. Chromatic aberrations are suppressed by the development of a supersonic Fe b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…For the final result one has to average over many realizations (typically 4000 trajectories). Between the spontaneous emission events the density-matrix elements evolve according to the set of differential equations (4) and the atomic motion is given by solving Newton's equation of motion with the instantaneous force given by equation (6). This evolution is implemented using a Runge-Kutta integration procedure of fourth order for a typical time step of δt ∼ 1 ns.…”
Section: Monte Carlo Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the final result one has to average over many realizations (typically 4000 trajectories). Between the spontaneous emission events the density-matrix elements evolve according to the set of differential equations (4) and the atomic motion is given by solving Newton's equation of motion with the instantaneous force given by equation (6). This evolution is implemented using a Runge-Kutta integration procedure of fourth order for a typical time step of δt ∼ 1 ns.…”
Section: Monte Carlo Methodsmentioning
confidence: 99%
“…Atomic nanofabrication, a technique of direct deposition of neutral atoms using conservative far off resonance atomlight interactions, has been intensively studied in recent years. Direct deposition has already been demonstrated for sodium [1], chromium [2] and aluminium [3] while experiments with gallium [4], caesium [5], iron [6] and indium are currently under construction. In all these experiments the structures are realized by a sinusoidal conservative potential acting as an array of cylindrical lenses for the atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Direct deposition atom lithography has been successfully applied to sodium atoms [18], aluminium atoms [43] and chromium atoms [20]. Laser cooling of technologically interesting candidates for nanostructures are currently investigated for iron [44] and for the group III atom gallium [45]. Indium is currently under investigation if the available optical transitions allow us to create a collimated indium beam [46].…”
Section: Other Materialsmentioning
confidence: 99%
“…7͒ atoms, and our group is pursuing it for Fe atoms. 8 In the case of Cr, an extensive study on structure widths was done by Anderson et al 9 They found that the structures deposited were always 20-30 nm wider than the incoming atomic beam flux distribution. Due to the confidence and thoroughness with which this atomic beam flux distribution can be calculated, they concluded that the broadening of the nanostructures must be caused by a diffusion process on the substrate.…”
Section: Introductionmentioning
confidence: 99%